2005
DOI: 10.1111/j.1365-2915.2005.00575.x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Ixodes ricinus in the British Isles: investigation of historical records

Abstract: Ixodes ricinus Linnaeus (Acari: Ixodidae) is the most abundant and widely distributed tick in the British Isles, and is a vector for a number of bacterial, viral and protozoal pathogens of both medical and veterinary importance. This report provides an update to the historical distribution data of I. ricinus, published by the Biological Records Centre (BRC), Monks Wood in The Provisional Atlas of the Ticks (Ixodidae) of the British Isles by K. P. Martyn (1988), and is supplemented with additional BRC records s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
46
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 19 publications
(21 reference statements)
4
46
0
Order By: Relevance
“…The ticks are relatively more abundant in woodland, heath and moorland habitats, but can be found even in urban areas like parks, where hosts are plentiful. Few studies have reported the presence of ticks in urban areas, but some authors have suggested that the abundance and distribution of ticks in urban areas has increased (PIETZSCH et al, 2005). The presence of ticks in all dogs of this study reinforces the risk of transmission of Brazilian Lyme-Like disease or Baggio-Yoshinari Syndrome agents to humans in the studied area.…”
Section: Resultssupporting
confidence: 62%
See 2 more Smart Citations
“…The ticks are relatively more abundant in woodland, heath and moorland habitats, but can be found even in urban areas like parks, where hosts are plentiful. Few studies have reported the presence of ticks in urban areas, but some authors have suggested that the abundance and distribution of ticks in urban areas has increased (PIETZSCH et al, 2005). The presence of ticks in all dogs of this study reinforces the risk of transmission of Brazilian Lyme-Like disease or Baggio-Yoshinari Syndrome agents to humans in the studied area.…”
Section: Resultssupporting
confidence: 62%
“…In this study, the WB was able to confirm the presence of Lyme Borreliosis in 54 (32.14%) dogs. This high prevalence may indicate the circulation of the etiologic agent in the northwestern region of Paraná state (MEAD et al, 2011;SMITH et al, 2012). Mead et al (2011) reported that a canine seroprevalence more than 5% is a sensitive but nonspecific marker of human risk, whereas seroprevalence lower or equal to 1% was associated with a minimal risk for human infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tick distribution is not necessarily determined by one factor alone, instead being influenced by several inter-related factors including climate, vegetation structure, and host distribution (Cumming 1999;Randolph 2000;Pietzsch et al 2005;Cumming 1999;Estrada-Peña 2003). Ticks are passive dispersers and must be transported (usually by hosts) to colonize new areas (Estrada-Peña 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In Europe ticks are the most important vector of zoonotic pathogens, which include Borrelia burgdorferi the agent of Lyme borreliosis and the tick borne encephalitis (TBE) complex of viruses. The abundance and distribution of Ixodes ricinus ticks in the British Isles are increasing (Scharlemann et al, 2008;Pietzsch et al, 2005;Kirby et al, 2004). Theoretically, reducing vector populations will mitigate disease incidence.…”
Section: Introductionmentioning
confidence: 99%